Comparison between diode laser and scalpel for lip lengthening in patients with gummy smile - Alan H Mawlood Qassab; Shehab A Hamad (College of Dentistry/ University of Baghdad, 2019)
Background: lip lengthening procedure is one of the surgical options for the correction of gummy smile in patients with short upper lip. Methods: A comparative clinical study was conducted on 15 patients requiring lip lengthening procedure for the esthetic correction of excessive gingival exposure with gummy smile. Scalpel was used in seven patients and diode laser in the remaining eight patients. Under infiltration anesthesia, about one cm strip of mucosa was excised at the vestibular depth and the mucosa of the lip was sutured to the alveolar mucosa. Results: The diode laser group demonstrated less postoperative pain and swelling. Regarding postoperative ecchymosis, three patients in the scalpel group developed ecchymosis and no cases were noted in the laser group, the difference was statistically significant. No patient in the laser group developed wound dehiscence and only one patient in the scalpel group had wound dehiscence at third postoperative day. Observed at one month postoperatively, the laser treated groups had less obvious scar than the scalpel group. Conclusion: Diode laser is a valuable tool in performing lip lengthening for gummy smile.